Analisis Materi Pembelajaran al-Qur’an Hadis Kelas IX Madrasah Tsanawiyah terkait Mad wa Qashar - Yelvi, Maulida; Adona, Putri (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Mad wa qashar are two important concepts in tajweed that relate to the length and shortness of the letters in the Qur'an. Properly understanding and applying mad wa qashar is essential to produce fluent recitation of the Qur'an. In this study, the author wants to analyse the material of mad wa qashar in learning al-Qur'an Hadith at Madrasah Tsanawiyah. The research method used is a qualitative method with a content analysis approach, the main source is the Al-Qur`an Hadith textbook published by the Ministry of Religion of the Republic of Indonesia. After conducting an in-depth analysis, the author can find the structure of the Al-Qur'an Hadith material in Madrasah Tsanawiyah related to mad wa qashar consists of two sub-themes. The two sub-themes are: i) The definition of Mad wa Qashar, ii) Types of Mad and examples. In the future, the author hopes that this research will have a positive impact, especially in madrasah as a formal educational institution with the characteristic of instilling Islamic values to its students